Organizational Change and the Imperatives of Managing Employee Resistance: A Conceptual Review - Tamunomiebi , Miebaka; Akpan, Enefiok (Journal of Strategic Management, 2021)
Purpose: The purpose of this paper was to critically examine the factors that engender employee resistance to change and the various organizational strategies aimed at managing employee resistance to change. Methodology: The paper is a conceptual review of literature and thus adopted a desk research methodology to review extant literature on the subject matter. Findings: based on reviewed literature, managing and leading employees in a changing environment is critical to overall business success. A significant problem for many business leaders is that they fear employee resistance and do not use resistance as an opportunity to engage and learn. Unique Contribution: This study provides meaningful insight to the strategies needed to manage change which is seen as a permanent business function to improve efficiency and keep organizations adaptable to the competitive marketplace. Recommendation: Organizations must act in a proactive manner in managing incivility so that it does degenerate to serious and corrosive consequences that eat away the workplace culture by promoting well-being in the workplace and preventing certain unsafe dynamics from establishing themselves.